Human Papillomavirus Cervical Infection and Associated Risk Factors in a Region of Argentina With a High Incidence of Cervical Carcinoma - S. A. Tonon; M. A. Picconi; J. B. Zinovich; D. J. Liotta; P. D. Bos; J. A. Galuppo; L. V. Alonio; J. A. Ferreras; A. R. Teyssié (Hindawi Limited, 1999)
Objective: To assess the prevalence and potential risk factors associated with human papillomavirus (HPV) cervical infection among women residing in a region of northeastern Argentina with a high incidence of cervical cancer.